THE RITUAL OF MARRIAGE - Manan, Abdul (Jurnal Ilmiah Peuradeun, 2014)
This article explores the mating rituals in Labuhan Haji West - South Aceh. The goal is to express the values and profound ideas expressed by Aneuk Jamee society before and after the wedding ceremony itself. This research is a field of research and data collection through observation with utmost care and in-depth interviews of key informants. The research concludes that men are more active than women. Therefore man is personified as "beetle" while women personified as â€œflowersâ€, passively waiting for â€œthe coming beetleâ€. Men planned marriage but women have the right to agree or not. Overall this ritual aims to obtain offspring. In regard to Islamic law represented by the priest, custom by Keuchik (village head), and the Old Village by Tuwo Ampek. But the overall picture of this ritual is the authority in carrying out the marital relationship is not derived from the father's brothers next door called the legal guardian of the brothers but next to the mother who called the niniak mamak.